Lonely Planet India (Travel Guide) (Lonely Planet Global, 2019)
With its sumptuous mix of traditions, spiritual beliefs, festivals, architecture and landscapes, your memories of India will blaze bright long after you've left its shores. Marvel at the intricate floral designs on the Taj Mahal, watch the setting sun cast a rosy glow over the otherworldly landscape of hampi, and listen to monks chanting in the shadow of the mighty Himalaya in Ladakh. Taj Mahal in 3D yoga, spas & spiritual pursuits volunteering planner this 18th edition covers: Delhi, Rajasthan, Kashmir, Ladakh, Agra, Varanasi, Himachal Pradesh, Bihar, Rishikesh, West Bengal, Darjeeling, Goa, Bengaluru (Bangalore), Mumbai (Bombay), Tamil Nadu, Chennai, Hyderabad, Kerala, Andaman islands and more.
Keywords: Travel Guid Book; India; Reference Book